Spatial analysis of hollow ways in the Hildesheimer Wald Mountains (Lower Saxony, Germany) as a model for mountainous regions of Central Europe - Kirchner, André; Hermann, Nico; Stadtmann, Robin (ERDKUNDE, 2020)
The Hildesheimer Wald is a subdued mountain range situated at the northern transition from the Central German Uplands to the North German Plains. Widespread hollow way systems are distinctive anthropogeomorphic features documenting the historical importance of the region in terms of traffic and land use issues. In this manuscript we focus on the detection of hollow ways and the quantification of the surface area affected by hollow ways. Therefore, we used i) pedo-morphological field mapping in two selected areas of the central Hildesheimer Wald Mountains. These two areas were additionally surveyed using ii) a semi-automated GIS-based modelling approach to compare both mapping methodologies. The analysis of the calculated hollow-way-affected surface areas shows only minor differences (2.8  % and 0.7  %) indicating the overall high potential of this GIS-approach to map and outline hollow way systems. The pedological investigations in the two selected areas demonstrate that the soilscape is largely transformed where hollow ways frequently appear. During the development phase of hollow ways, concentrated surface runoff led to strong erosional processes at the hollow way bottoms and subsequently relatively shallow soils. In consequence, there is a remarkable loss of forestry area at degraded hollow way bottom sites, suggesting reduced usability for commercial forestry. In the second part of the study we used the GIS-mapping approach to calculate the hollow-way-affected surface area for the forested area of the entire Hildesheimer Wald Mountains. We ascertained an area of 183 ha representing approximately 2.2 % of the total mountain range. Due to methodological limitations in very shallow pronounced hollow way sections it is very likely that this value is a rather conservative approximation of the real extent of hollow way systems. Since hollow ways represent preservable environmental archives storing information on cultural landscape development, we are strongly in favor of the implementation of protection measures in these specific areas. Hollow way systems should be managed adequately to avoid further degradation and additionally increase the quantity and quality of wildlife habitats.